(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate the risk factors and management of femoral fractures related to birth trauma. Study Design: Descriptive Case series Study Place and Duration of Study: This study was conducted in Department of Orthopaedics& Traumatologyand Department of Obstetrics & Gynecology of Khyber Teaching Hospital, Peshawar from April 2008 to March 2013. Materials and Methods: Over a period of 5 years,cases of femoral fractures in newborns due to birth trauma presenting to Orthopaedic&Taumatologydepartment or occurring in Obstetrics & GynecologyDepartment of Khyber Teaching Hospital Peshawar were recruited to the study. Birth histories of the cases were explored with respect to period of gestation, birth weight, presentation at birth and mode of delivery.Type of fracture and management used was documented. Cases were followed till recovery. Results: Mean gestational age was 38.1 weeks and mean time to diagnose was 3 days. Presentation of baby was breech and mode of delivery was Caesarean section in majority of cases.Mid shaft fracture was present in ten cases and three had subtrochanteric fracture. All patients showed complete union at a mean duration of 3.2 weeks. Conclusion: Femoral fracture due to birth trauma in newborn is a rare injury. It is more common in cases of Caesarean section done for breech presentation. Risk is high in preterm and/or low birth weight babies. Fracture mostly involves shaft of femur.These fractures have very good prognosis and show complete healing following immobilization